Efficiency, Fairness and Sustainability in Social Housing Policy and Projects - Napoli, Grazia; Trovato, Maria Rosa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The provision of affordable housing for low-income households is a very complex issue that has long been debated in many countries around the world. Social housing (SH) is one of the tools for achieving fairness, social sustainability, and economic feasibility, and it is interrelated with politics, ethics, and economics, as well as the environment, architecture, and technology. In other words, national and local policies, as well as public and private financial resources, are all needed to provide SH.SH also involves social and urban transformations and is, consequently, linked to urban planning and redevelopment projects, real estate market dynamics, and cooperation between public and private stakeholders. Furthermore, decision-making on SH policies and projects has to be supported by assessments of economic feasibility and social and environmental sustainability.This volume presents studies on various topics to recompose the multi-faceted subjects of social housing within a unified framework.